Research progress in the etiology and the treatment of erythroderma - Lingyu HU; Fuqiong JIANG; Ruiting HUANG (Pifu-xingbing zhenliaoxue zazhi, 2023)
Erythroderma is a rare and severe skin disease, characterized by erythema and scaly rashes all over the body, with the involvement of over 90% of the body surface area. Due to the complex etiologies, unclear pathogenesis, numerous complications and severe clinical symptoms, and no special and effective treatment, erythroderma is often missed diagnosis or misdiagnosed. In this paper, we systematically review the pathogenesis, progress, etiology, clinical features, diagnosis, treatments, and prognosis of erythroderma, providing ideas for rational diagnosis and effective therapies of erythroderma.